Evaluation of anxiety, depression and quality of life using the hospital anxiety & depression scale and glaucoma quality of life-36 in juvenile open angle glaucoma patients - Rahman, Siti Khadijah Abdul (2021)
Introduction Glaucoma is the leading cause of blindness worldwide with a large number from Asia and Africa continents. Juvenile Open-Angle glaucoma is a rare subset of Primary open-angle glaucoma. It is usually diagnosed between the age of t 5 to 35 years old and predominantly affecting men. The effect of glaucoma on quality of life, anxiety and depression have been shared by the previous studies. However, there are very few studies published specifically on the juvenile open angle glaucoma group. Purpose: This study aims to evaluate anxiety, depression and quality of life in among JOAG patients as compared to control. It also serves to identify factors affecting anxiety, depression and quality of life among JOAG patients in Malaysia. Material and Method: The Hospital Anxiety and Depression Scale (HADS) questionnaire and Glaucoma-Quality of Life 36 (GlauQOL-36) questionnaire were administered to 68 Juvenile Open Angle Glaucoma (JOAG) patients and 202 controls to evaluate their anxiety, depression and quality of life. Sociodemographic of both groups were evaluated. The clinical features of JOAG patients were further evaluated. Univariate and multivariate analysis were done using simple linear and multiple linear regression respectively on the variables to look at factors affecting anxiety, depression and quality of life. Results: The mean score for HADS-A and HADS-D and GlauQOL-36 among JOAG patients were, 6.31 (4.04), 5.53 (4.017) and 69.85 (10.43) respectively, while the mean among controls were 3.20 (3.71), 3.27 (3.64) and 83.29 (7.98) respectively. The scores among JOAG were significantly lower than control in all domains, namely daily life, driving, psychological wellbeing, self-image, anxiety, treatment burden and confidence in health care. The significant factor to account for the increase in HADS-D score were tertiary education (p=0.009), poorer MD worst eye (p=0.013) and shorter duration of diagnosis (p=0.012). The significant factor associated with better GlauQOL-36 were female (p=0.052), income more than USD 500 (p= 0.036) and the use of topical carbonic anhydrase inhibitor (CAI) (p=0.005). Conclusion: The JOAG patients were significantly more affected in terms of anxiety, depression and quality of life as compared to the control group. The factors associated with depression were tertiary education, poorer MD worst eye (p=0.013) and shorter duration of diagnosis The significant factor associated with better GlauQOL-36 were female, income more than USD 500 and the use of topical carbonic anhydrase inhibitor (CAI). The use of questionnaire in clinical setting may help in having a holistic evaluation of glaucoma patients. Healthcare providers need to pay attention to the Quality of Life and the psychological aspect of this group of patients and formulate personalised care.